Late preterm infants: modern trends and challenges - Srivastava, Alice; Shevtsova, Tetiana (The Ukrainian Scientific Medical Youth Journal, 2025)
late preterm infants, born between 34 0/7 and 36 6/7 weeks of gestation, constitute a significant subgroup of preterm infants, accounting for nearly 75% of all preterm births. Although late preterm infants are often perceived as physiologically closer to term infants, they are at increased risk of morbidity and mortality due to developmental and structural immaturity. Recent studies suggest that preterm infants are at high risk of impaired postnatal adjustment and are prone to complications affecting multiple organ systems, including respiratory disease, feeding difficulties, hypoglycemia, hyperbilirubinemia, temperature instability, sepsis, nervous system damage, and neurodevelopmental delay. Late preterm infants are more likely to have neurodevelopmental impairment compared to term infants, with potential long-term consequences extending into later life, such as cognitive delay, language delay, higher risk of cerebral palsy and attention deficit hyperactivity disorder, autism. The incidence of late preterm birth is increasing worldwide, resulting in increased healthcare costs and resource utilization. The aim of this article is to present a literature review of current trends, challenges, and advances in the care of preterm infants, focusing on their unique comorbidities, developmental risks, and to demonstrate that these preterm infants are at increased risk of maladjustment, morbidity, and mortality during and after the neonatal period compared to term infants. A systematic search of scientific publications in various databases was conducted to identify modern approaches to the management of late preterm infants. The information obtained was systematized and integrated to identify the main risks of maladjustment and features of further development in this group of infants. Early diagnosis, observation and treatment of pregnant women with chronic diseases and pathologies during pregnancy and childbirth, timely detection of high-risk pregnancies, effective antenatal diagnostics and high-quality neonatal care are the main directions of modern perinatology that can improve the prognosis of "late preterm" newborns. A comprehensive approach, including minimizing unnecessary late preterm births, careful assessment, optimized treatment, parental education and follow-up care, is essential for improving outcomes and reducing long-term risks. This review highlights the importance of evidence-based prevention and treatment strategies, while calling for further research to improve outcomes in this vulnerable group of infants.